World Heart Federation Consensus on Transthyretin Amyloidosis Cardiomyopathy (ATTR-CM) - Dulce Brito (Chair); Fabiano Castro Albrecht; Diego Perez de Arenaza; Nicole Bart; Nathan Better; Isabel Carvajal-Juarez; Isabel Conceição; Thibaud Damy; Sharmila Dorbala; Jean-Christophe Fidalgo; Pablo Garcia-Pavia; Junbo Ge; et al. (Ubiquity Press, 2023)
Transthyretin amyloid cardiomyopathy (ATTR-CM) is a progressive and fatal condition that requires early diagnosis, management, and specific treatment. The availability of new disease-modifying therapies has made successful treatment a reality. Transthyretin amyloid cardiomyopathy can be either age-related (wild-type form) or caused by mutations in the TTR gene (genetic, hereditary forms). It is a systemic disease, and while the genetic forms may exhibit a variety of symptoms, a predominant cardiac phenotype is often present. This document aims to provide an overview of ATTR-CM amyloidosis focusing on cardiac involvement, which is the most critical factor for prognosis. It will discuss the available tools for early diagnosis and patient management, given that specific treatments are more effective in the early stages of the disease, and will highlight the importance of a multidisciplinary approach and of specialized amyloidosis centres. To accomplish these goals, the World Heart Federation assembled a panel of 18 expert clinicians specialized in TTR amyloidosis from 13 countries, along with a representative from the Amyloidosis Alliance, a patient advocacy group. This document is based on a review of published literature, expert opinions, registries data, patients' perspectives, treatment options, and ongoing developments, as well as the progress made possible via the existence of centres of excellence. From the patients' perspective, increasing disease awareness is crucial to achieving an early and accurate diagnosis. Patients also seek to receive care at specialized amyloidosis centres and be fully informed about their treatment and prognosis.